At the nexus of data and collections: New affordances in the age of mass-scale digital libraries - Downie, J; Lorang, E; Soh, L; Bainbridge, D; McIntyre, S; Page, K (Association for Computing Machinery, 2018)
Within the context of mass-scale digital libraries, this panel will explore methodologies and uses for-as well as the results of- conceiving of "data as collections" and "collections as data." The panel will explore the implications of these concepts through use cases involving data mining of the HathiTrust Digital Library, particularly major projects developed at the HathiTrust Research Center. Featured will be the Workset Creation for Scholarly Analysis + Data Capsules (WCSA+DC) project, the Solr Extracted Features project, and the Image Analysis for Archival Discovery (Aida) project. Each of these projects focuses on various aspects of text, image and data mining and analysis of mass-scale digital library collections.